Energy Clustering during Uzbekistan’s Energy Transition - Olga V. Radionova; Rashid A. Sitdikov; Surayyo B. Talipova (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Uzbekistan's modern energy sector, like global energy, is characterized by the process of energy transition towards alternative energy and is accompanied by innovative processes related to energy clustering. This creates a need to analyze the effectiveness of the cluster approach, the emerging synergy in implementing the energy transition, and for the further development of the energy sector. The article examines the cluster approach for the effective development of the energy sector during Uzbekistan's energy transition. An analysis of the creation of energy clusters based on alternative and renewable energy sources (ARE) has been conducted. Proposals have been developed for organizing energy clusters in Uzbekistan to rationalize the energy transition and further develop the electricity sector. Aim: to analyze and determine the conditions for using the cluster approach during Uzbekistan's energy transition and for the development of the republic's energy sector based on its clustering. Methods: international experience in creating energy clusters, as well as the potential of Uzbekistan's energy sector, are analyzed and utilized. Results: proposals have been developed for the creation of energy clusters during the implementation of Uzbekistan's energy transition and for the further development of the republic's energy sector.